Pemimpin Gereja Visioner Pelaku Perubahan - Sri Wahyuni (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
This article departs from the condition of some churches which are very concerning. Not a few churches live reluctantly, don't want to die, there are even churches that are quiet about activities, even if there are only routines, especially during the covid-19 pandemic like now, especially small churches in villages. Silence, waiting for a helping hand from the benefactors. Therefore, this article will discuss the importance of the role of a Church leader as an agent of change for the congregation he pastors. This study uses a literature method with a descriptive qualitative approach. The emphasis is on the study of library sources and parsing them and providing explanations in a descriptive framework. The main source analysis is literature literacy which examines visionary Church leaders as agents of change which is complemented by various journal articles and other academic sources relevant to the topics discussed. Vision is an important thing that must be owned by a church leader, because the vision will provide a clear direction. Vision is one of the determining factors for the success of a leader.